Problem-Based Learning Model with Video Media to Improve Writing Skills - F. Siburian; Sutama Sutama (Indonesian Journal Of Educational Research and Review, 2021)
Students are less interested in writing because teachers tend to use textbooks as the only medium in learning. This has an impact on students' low writing skills. The purpose of this study is to analyze the problem-based learning model assisted by video learning. to improve critical response text writing skills. This type of research is classroom action research. This study follows the stages of classroom action research, each cycle consisting of four stages, namely planning, action, observation, and reflection. The subjects of this research were 28 students of class IX. Methods The methods used to collect data are observation, interviews, and tests. The instruments used to collect data are questionnaires and test sheets. The data analysis used in this research is descriptive qualitative and quantitative descriptive analysis. The results showed that the application of the problem-based learning model assisted by video media could improve students' critical response text writing skills. The increase in the average score of critical response text writing skills is 11, from an average of 80 to 91. So, learning can be said to be successful because overall, students are complete. Students also gave a very positive response in participating in learning to write critical response texts by applying a problem-based learning model assisted by video media with a score of 22.89.